1966
DOI: 10.1149/1.2423879
|View full text |Cite
|
Sign up to set email alerts
|

The Heat-Treatment of Anodic Oxide Films on Tantalum

Abstract: Dielectric measurements have been made on tantalum which has been anodically oxidized in aqueous phosphoric acid of various concentrations and then heated in air. The resulting dielectric consists of a highly conducting portion adjacent to the tantalum and an outer, nonconducting portion. This structure is interpreted in terms of the distribution of phosphorus incorporated into the oxide and its effect on the diffusion of oxygen during heat‐treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Therefore, if niobium capacitors are used, the size could be smaller than that of tantalum capacitors for the same performance. However, anodic oxide films on niobium have dielectric properties that are unsuitable for capacitors: (i) there are increases in capacitance and leakage current by heat treatment [2][3][4][5][6][7][8][9][10][11][12], and (ii) there is a bias voltage dependence of the capacitance [11][12][13][14][15][16][17][18]. A previous investigation reported that these properties are caused by imperfections in the anodic oxide films, which are grown by heat treatment [10] or by potentiostatic anodizing [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if niobium capacitors are used, the size could be smaller than that of tantalum capacitors for the same performance. However, anodic oxide films on niobium have dielectric properties that are unsuitable for capacitors: (i) there are increases in capacitance and leakage current by heat treatment [2][3][4][5][6][7][8][9][10][11][12], and (ii) there is a bias voltage dependence of the capacitance [11][12][13][14][15][16][17][18]. A previous investigation reported that these properties are caused by imperfections in the anodic oxide films, which are grown by heat treatment [10] or by potentiostatic anodizing [13].…”
Section: Introductionmentioning
confidence: 99%
“…34,35 This analysis resulted in calculated donor densities ranging from 8 × 10 18 /cm 3 for as-anodized samples to 2 × 10 18 /cm 3 for oxidized and annealed samples. 36 The described electrical response of as-anodized and annealed niobium anode capacitor samples is in contrast with the early work of Smyth et al 20,[37][38][39][40] who examined the effect of elevated temperatures on the electrical performance of the Ta/Ta 2 O 5 -and Nb/Nb 2 O 5 -systems in detail. During their comprehensive studies they were able to demonstrate that the temperature dependence of the capacitance of as-formed Nb 2 O 5 films is much higher than for the comparable tantalum case.…”
Section: Bias-dependence Of Mass-specific Charge Q/m Anodementioning
confidence: 95%
“…Since the specific conductivity of 18 wt% H 2 SO 4 is significant high, any influence of the measuring electrolyte conductivity on capacitance measurements can be excluded. 20 The measurements were performed at f = 120 Hz with bias voltages ranging from−0.5 V to 15 V. All measured capacitances C meas. were transformed into specific charge values Q according to Q = C meas ·U ox .…”
Section: Electrical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations